2001
DOI: 10.1046/j.1365-2605.2001.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between computerized slow‐stage and static liquid nitrogen vapour freezing methods with respect to the deleterious effect on chromatin and morphology of spermatozoa from fertile and subfertile men

Abstract: The purpose of this study was to determine the negative effects (cryodamage) on human spermatozoa after freeze-thawing and to determine whether freeze-thawing of spermatozoa with a programmed slow freezer is better than freezing with liquid nitrogen vapour (rapid freezing) with regard to alterations in sperm chromatin and morphology in semen from fertile (donor) and subfertile, IVF/ICSI, patients. Ninety-five semen samples were obtained either from patients attending our IVF unit for treatment (n=34) or from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 32 publications
2
34
0
1
Order By: Relevance
“…Damage to sperm DNA can be caused by intrinsic factors like protamine deficiency, mutations that compromise DNA packaging, aging, reactive oxygen species and an incomplete process of apoptosis during spermatogenesis (Gatewood et al 1990, Sakkas et al 2003, Singh et al 2003. External factors that result in sperm DNA damage include heat (Paul et al 2008), chemotherapeutics (Delbes et al 2007), radiation (Sailer et al 1995, Aitken et al 2005, pollution (Rubes et al 2005) and age (Singh et al 2003) as well as in vitro semen processing factors like type of extender, prolonged incubation time (Krzyzosiak et al 2000) and cryopreservation (Hammadeh et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Damage to sperm DNA can be caused by intrinsic factors like protamine deficiency, mutations that compromise DNA packaging, aging, reactive oxygen species and an incomplete process of apoptosis during spermatogenesis (Gatewood et al 1990, Sakkas et al 2003, Singh et al 2003. External factors that result in sperm DNA damage include heat (Paul et al 2008), chemotherapeutics (Delbes et al 2007), radiation (Sailer et al 1995, Aitken et al 2005, pollution (Rubes et al 2005) and age (Singh et al 2003) as well as in vitro semen processing factors like type of extender, prolonged incubation time (Krzyzosiak et al 2000) and cryopreservation (Hammadeh et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This clarification is necessary given the ambiguous results found in the literature. Some have suggested that the highly stable DNA is fragmented by freeze-thawing [Royere et al 1988;Sakkas et al 1999;Hammadeh et al 2001]. However, other authors have differed [Steele et al 2000].…”
Section: Discussionmentioning
confidence: 99%
“…Acridine-Orange Staining Assay: Sperm DNA integrity was assessed using the AO fluorescence method (11). Air-dried slides were fixed overnight in freshly prepared Carney's solution (three parts of methanol and one part of glacial acetic acid) and allowed to air dry for a few minutes.…”
Section: Semen Collection and Cryopreservationmentioning
confidence: 99%
“…The success of cryopreservation of cells is affected by the rate of freezing (10,11) and the composition of the solution where the cells are frozen (11,16). When the cells are rapidly cooled, water is not lost fast enough to maintain the equilibrium; the cells become increasingly supercooled and freeze intracellulary, and this process might affect the integrity of chromatin and the morphology of spermatozoa (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation